The impact of improving suicide death classification in South Korea: a comparison with Japan and Hong Kong. - Chee Hon Chan; Eric D Caine; Shu Sen Chang; Won Jin Lee; Eun Shil Cha; Paul Siu Fai Yip (PLoS ONE, 2015)
The suicide rate of South Korea has increased dramatically during the past decades, as opposed to steadily decreasing trends in Japan and Hong Kong. Although the recent increase of suicide in South Korea may be related to changing socioeconomic conditions and other contextual factors, it may also reflect, in part, a reduction of misidentified suicide cases due to improving classification of manner of death.We compared the annual proportional change of suicide, undetermined death, and accidental death from South Korea with those of Japan and Hong Kong from 1992 to 2011; a greater proportional change of the manner-of-death categories during the period is indicative of a relatively less stable registration and hence a greater potential for misclassification bias on reported suicide trends. Subgroup analyses stratifying the deaths by methods were also conducted. To estimate the impact, the age-standardized rates of these three death categories in each site were calculated.We found that, during the 20-year observation period, the proportional change of suicide, undetermined death, and accidental death in South Korea was significantly greater than Japan and Hong Kong. Similar observations were made in subgroup analyses. While death rates of the three manners in Japan and Hong Kong generally moved in a parallel fashion, the increase of suicide in South Korea occurred concomitantly with a significant reduction of its accidental death rate. 43% of the increase in suicides could be attributed to the decrease in accidental deaths, while 57% of the increase could be due to fundamental causes.Our data suggest that, during the mid-1990s and after, the increasing burden of suicide in South Korea initially was masked, in part, by misclassification. Thus, the later apparently rapid increase of suicides reflected steadily improving classification of manner of death, as well as a more fundamental increase in the suicide rate.